Creation of an E-commerce Mobile Application - MAZOUZI, AYMENE MOUNSSIF; Supervised : LOUNNAS, Bilal (University of M'sila, 2021)
E commerce is the process of doing business electronic. It changes the entire business scenario due to the powerful innovation of Internet, which is spreading fast through the world. The objective of this work is to design and build an e-commerce mobile application that can help the company keeping the customers up to date with new arrives and prices an promotions and make them expand . In order to develop this application we have chosen the latest technologies. For the fronted-end we picked “Flutter” which can make create Beautiful UI in No-Time . and for the back-end we picked “Node js” which is powerful and super fast .
Keywords: E-commerce , Mobile application